Strength training against resistance: how to determine the training zones - Ayllon, F. N.; Gutiérrez, A. J. (Journal of Human Sport & Exercise, 2007)
The strength training, using resistance that act by means of the gravity (free weights, handle machines, etc.) or other forms (hydraulic machines, elastic band, means, etc.), at the moment an activity is considered essential to guarantee a suitable physical yield applied to any sport, the mobility and the operation of the locomotive apparatus, as well as to improve functional independence in greater people. The objective of this one I articulate is to propose a methodology of training of the different types from based strength, as much in the magnitudes of the weights mobilized like in the reached speed and the mechanical power produced in each action or movement.